Investigators' viewpoint of clinical trials in India: Past, present and future - Mallath, Mohandas K. (Perspect Clin Res, 2017)
India's success in producing food and milk for its population (Green Revolution and White Revolution) happened because of scientific research and field trials. Likewise improving the health of Indians needs clinical research and clinical trials. A Large proportion of the sick Indians are poor, illiterate with no access to good health care. They are highly vulnerable to inducement and exploitation in clinical trials. The past two decades saw the rise and fall of clinical trials in India. The rise happened when our regulators created a favorable environment, and Indian investigators were invited to participate in global clinical trials. The gap between the demand and supply resulted in inadequate protection of the trial participants. Reports of abuses of the vulnerable trial participants followed by public interest litigations led to strengthening of regulations by the regulators. The stringent new regulations made the conduct of clinical trials more laborious and increased the cost of clinical trials in India. There was a loss of interest in sponsored clinical trials resulting in the fall in global clinical trials in India. Following repeated appeals by the investigators, the Indian regulators have recently relaxed some of the stringent regulations, while continuing to ensure the adequate patient protection. Clinical trials that are relevant to our population and conducted by well-trained investigators and monitored by trained and registered Ethics Committees will increase in the future. We must remain vigilant, avoid previous mistakes, and strive hard to protect the trial participants in the future trials.